2017
DOI: 10.3171/2017.4.peds171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of higher implant density on curve correction in dystrophic thoracic scoliosis secondary to neurofibromatosis Type 1

Abstract: OBJECTIVEThe aim of this study was to investigate how implant density affects radiographic results and clinical outcomes in patients with dystrophic scoliosis secondary to neurofibromatosis Type 1 (NF1).METHODSA total of 41 patients with dystrophic scoliosis secondary to NF1 who underwent 1-stage posterior correction between June 2011 and December 2013 were included. General information about patients was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 22 publications
2
34
0
Order By: Relevance
“…The clinical outcome of dystrophic scoliosis patients treated with posterior-only fusion by using hooks and rods demonstrated that the pseudarthrosis rate was high and curve progression was common [17]. Recently, some good results of posterior only fusion surgeries in NF-1 patients with dystrophic scoliosis have been reported [9,10,19]. In this study, we reported our results about the posterior only fusion procedure in NF-1 patients with EOS.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The clinical outcome of dystrophic scoliosis patients treated with posterior-only fusion by using hooks and rods demonstrated that the pseudarthrosis rate was high and curve progression was common [17]. Recently, some good results of posterior only fusion surgeries in NF-1 patients with dystrophic scoliosis have been reported [9,10,19]. In this study, we reported our results about the posterior only fusion procedure in NF-1 patients with EOS.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, it has been found that higher density of pedicle screw placement can help to improve the postoperative correction rate of EOS in NF-1patients [10,19]. We can only perform regular fluoroscopy due to the lack of O-arm at the early stage of our study, which made it difficult to place the pedicle screws.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17Recently, some good results of posterior only fusion surgeries in NF-1 patients with dystrophic scoliosis have been reported. (9,10,19) In this study, we reported our results about the posterior only fusion procedure in NF-1 patients with EOS.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the posterior only instrument fusion was reported to be used to treat dystrophic scoliosis in NF-1 patients because challenges for the anterior approach caused by the extensive plexiform tumors could be avoided by using posterior approach and a good short-term result from posterior approach has been reported. (9, 10) In Li and his colleagues' study, the posterior only approach demonstrated a good short-term result to treat early-onset scoliosis (EOS) in a group of NF-1 patients with an average age of 13 (the youngest patient was 8 years old), but the number of included patients were not addressed (10). However, it is rarely reported whether posterior spinal fusion will achieve a good midlong-term result in patients at young age (age<10Yrs) (11).…”
Section: Introductionmentioning
confidence: 99%